“O flagelo que nos ameaça”: o cólera na província mineira, epidemia e mobilização social (1855-56) - Ana Carolina Rezende Fonseca (2014)
Studies on the history of health and diseases have been seeking to think over several dimensions of the diseases. They are not limited to medical and scientific aspects, but also cover a wide range of issues, considering that the interpretations of the diseases – and the impacts caused by them – were a social construction involving cultural, political and economic factors. This work focuses on the first epidemic outbreak of cholera occurred in Minas Gerais in the nineteenth-century (1855-1856). It attempts to understand the lived experience during that outbreak through the analysis of medical and administrative authorities’ statements, theories that explained the origin and nature of cholera as well as the proposals and actions aiming to confront the disease.